Penyuluhan Gizi Seimbang Anak Usia Sekolah Pada Siswa-Siswi SD Negeri 27 Kartiasa Kabupaten Sambas - Mega Fitri; Tasya; Sri Yuliani; Leni; Maria Felixia Randong; Pegi Aryasari; Adi Putra Ramdani (PPPM POLITEKNIK NEGERI SAMBAS, 2022)
Indonesian faces various health-related problems, one of which is the lack of balanced nutrition. Nutrients can affect the level of health, intelligence, and high work productivity. Counseling at SD Negeri 27 Kartiasa, Sambas Regency aims to increase the knowledge of elementary school children about balanced nutrition intake patterns. The method used in this activity is lecture and question and answer. The process of this activity lasts for ± 1 hour. The results of this activity showed that students at SD Negeri 27 Kartiasa were very enthusiastic in participating in counseling activities. The students listen well when delivering the material, so that there is interaction between one another. With this balanced nutrition education counseling, it is hoped that students can apply a healthy lifestyle and consume healthy food and drinks according to their needs. Through this activity, students can find out a balanced nutritional intake that should be consumed according to their age and body condition.